Konflik Sosial dalam Novel Keberangkatan Karya Nh.Dini - Handayani, Guswira; Nurizzati, Nurizzati (Persona: Kajian Bahasa dan Sastra, 2024)
The aim of this research is to explain: (1) the form of social conflict in the novel Keberangkatanby Nh. Dini, (2) the causes of conflict in the novel Departure by Nh. Dini, (3) the impact of conflict in the novel Departure by Nh. Early. The object used in this research is the novel Departure by Nh. Dini edition 9, published February 2023. This research is literary research using descriptive methods. Data collection techniques include reading and understanding novels, marking novels that are related to research questions, and carrying out data inventory. Data analysis techniques include data classification, data analysis and interpretation, research completion, and writing analysis results reports. Based on the results of data analysis, (1) the form of social conflict in the novel Keberangkatan Karya Nh. Dini consists of (a) personal (individual) conflict (b) group conflict, and c) community conflict (2) the causes of social conflict are classified into four categories: (a) differences between individuals (individuals), (b) differences in social class, (c) differences in interests, and (d) social change. (3) The impact of social conflict can be differentiated into three areas: (a) destruction of group unity, (b) changes in individual personality, and (c) destruction of values and norms.